(untitled) (Scientific journal of the Fergana State University, 2023)
This article reveals the important role of the family among the social relations of the society. It is scientifically based that the family, as a social and psychological group, performs the function of the main social unit of the society. With this, a socio-philosophical analysis of the socialization of the individual in family interpersonal relations and his connection with the ethnic-cultural values of all his generations has been made.